2012
DOI: 10.1021/jz300480w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Surface-Functionalized WS2 Nanosheets and Performance as Li-Ion Battery Anodes

Abstract: Separation of bulk tungsten disulfide (or WS2) into few-layer two-dimensional (2-D) crystals is of interest because of their high surface area for certain chemical processes and size-dependent optical and electronic characteristics. Herein, we demonstrate a process that involves the physical separation of weakly bonded WS2 layers by use of a strong acid treatment (chlorosulfonic acid) at 2 mg/mL, followed by quenching in deionized (DI) water. X-ray photoelectron spectroscopy of the superacid-treated WS2 sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
245
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(257 citation statements)
references
References 32 publications
12
245
0
Order By: Relevance
“…Electrodes prepared from hydrothermally synthesized MoS 2 nanoflakes and nanoplates exhibited capacities of as high as 1000 mAh −1 g −1 [140] and 1062 mAh −1 g −1 [141], respectively. WS 2 nanosheets and nanoflakes also show good reversible capacity [142][143][144]. Julien et al [145] have shown that 0.6 mol of Li ions intercalates per mole of WS 2 .…”
Section: Lithium and Sodium Ion Batteriesmentioning
confidence: 99%
“…Electrodes prepared from hydrothermally synthesized MoS 2 nanoflakes and nanoplates exhibited capacities of as high as 1000 mAh −1 g −1 [140] and 1062 mAh −1 g −1 [141], respectively. WS 2 nanosheets and nanoflakes also show good reversible capacity [142][143][144]. Julien et al [145] have shown that 0.6 mol of Li ions intercalates per mole of WS 2 .…”
Section: Lithium and Sodium Ion Batteriesmentioning
confidence: 99%
“…Tetraalkylammonium thiotungstates are precursors for WS 2 catalysts [7,[15][16][17]. WS 2 can be also used as gas sensor [6,[19][20], dry lubricant [21,22] and in lithium batteries [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…4a. Deposition of the clusters on top of graphene A stock dispersion of graphene was prepared by sonication of graphite (1 g) in 100 cm 3 of IPA with a Fisher Scientific sonic tip (nominal power 500 W, working at 40% amplitude, with pulses of 5 s length for 8 h). 9 The mixture was distributed in 50-cm 3 centrifuge tubes, and centrifuged in a Heraeus Multifuge centrifuge at 3500 rpm for 90 min.…”
Section: Dissolution Of the Platelets And Clusters Releasingmentioning
confidence: 99%
“…Two-dimensional (2D) materials have emerged as promising candidates for a broad range of applications, which include energy storage, [1][2][3][4] catalyst supports, 5,6 transistors 1,4,7,8 or drug delivery agents. 9,10 There has been intense research to define suitable routes for the production of ultrathin nanosheets of layered materials, based either on the exfoliation of the bulk compounds by different techniques 4,[11][12][13][14][15][16][17] or on the growth of the 2D materials from molecular precursors via chemical vapour deposition 18,19 and wet chemistry methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation